SISTEM PENDUKUNG KEPUTUSAN KENAIKAN KELAS (STUDI KASUS SDN 060 PEKKABATA KABUPATEN POLEWALI MANDAR PROPINSI SULAWESI BARAT) - Rosmawati Tamin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2015)
Decision support system is a system that can aid decision-making through the use of data and decision models to solve problems that are semi-structured and unstructured decision to provide alternative options and can produce solutions faster and more reliable results. Decision support systems are also designed so that it can be used easily by people who do not have basic computer operations capabilities and their implementation in the field of higher education. In supporting the completion of this field, the role of computer technology is very important to be applied as a support in information management and decision-making fast, effective and efficient. One critical decision is the decision-making, especially in school grade. This decision has many indicators in the determination. Frequent delays in the determination of the increase in class because of slow processing inputted data as an indicator. The increase in the improper class will have a considerable influence on the acceptance of the subject matter to a higher grade level because of a student's academic condition is not yet at that level, so the teacher will have difficulty in providing the subject matter